Dyslipidaemia pattern amongst diabetic patients visiting a tertiary care hospital in Eastern Odisha - Behera, Surendra Nath; Patro, Shubhransu (International Journal of Advances in Medicine, 2017)
Background: With controlled blood sugar levels, the occurrence of dyslipidaemia can be reduced. Due to poor awareness and literacy being a major concern, there is an association in the incidence of dyslipidaemia and cardiovascular risk. Routine and timely observations can help health care professionals to reduce the future risk. Methods: The current study was initiated at the Department of Medicine, KIMS, Bhubaneswar (Odisha). It included in total 669 patients, who were assigned into two groups: Group 1(Diabetic) included 364 patients and Group 2 (Non-diabetic) included 305 patients. The study patients were screened using a pretested structured questionnaire. The plan and checklist were linked by unique identification code (ID). Data was gathered in a friendly atmosphere after obtaining informed consent. Results: In the current study, all characteristics of diabetes were correlated with each parameter and it was found that disproportionate body mass index, high waist girth was correlated with incidence of cardiovascular disease (CVD). Literacy is one of the factor found intermediate responsible for CVD. The more educated, the more advances in current lifestyle is observed whereas due to illiteracy, awareness about health issues is less and both together result in increased incidence of CVD. Conclusions: Dyslipidaemia should be promptly diagnosed and treated aggressively to reduce the rate of morbidity and mortality in diabetic patients.